ANALISIS KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS VIII DALAM MENYELESAIKAN SOAL CERITA BARISAN DAN DERET ARITMETIKA DITINJAU DARI TIPE KEPRIBADIAN EKSTROVERT DAN INTROVERT DI SMPN 2 LEMBO: Analysis of Problem Solving Ability of Class VIIIStudents in Solving Story Questions OnArithmetic Lines and Series Used From Extrovert and Introvert Personality Types At SMPN 2 Lembo - Tumongka, Wiwik Andriani; Karniman, Tegoeh S.; Hadjar, Ibnu; M, Bakri (Jurnal Elektronik Pendidikan Matematika Tadulako, 2024)
This study aims to analyze the problem solving ability of students with extroverted and introverted personalities in solving arithmetic ranks and series problems in class VIII SMPN 2 Lembo using Polya's steps. This type of research is qualitative research. The subjects of this study were 4 students taken from 25 students in class VIII of SMPN 2 Lembo. The research subjects were one student with extroverted personality type for very high level (VKL), one student with extroverted personality type for low level (AGT), one student with introverted personality type for very high level (PJL), one student with introverted personality type for low level (JFCT). The results showed that the analysis of the problem solving ability of extroverted and introverted students in solving story problems of arithmetic rows and series, namely: 1) on the indicator of understanding the problem, very high ability extroverted VKL and introverted PJL students are able to explain and mention the information known and asked in the problem, but low ability extroverted AGT and introverted JFCT students need to read the problem several times to understand the problem, 2) indicators of making plans, very high ability extroverted VKL and introverted PJL students are able to make plans using the information they get, but low ability extroverted AGT and introverted JFCT students do not know the formula to be used in the story problem and in making plans cannot relate and complete between what is known and asked so that they cannot choose a strategy that suits the problem, 3) in the third indicator, very high ability students VKL extroverts and PJL introverts are able to carry out the solution plan appropriately and PJL introverts are very thorough in completing the solution plan, while low ability students AGT extroverts and JFCT introverts cannot solve the problems given appropriately. 4) at the stage of re-examining the answer, extrovert VKL, introvert PJL, and introvert JFCT re-examine the answer before collecting, but extrovert AGT students do not re-examine their answers before collecting.